Gestão de tecnologias em oftalmologia - Santos, Carla Ribeiro da Silva [UNIFESP] (2016)
Purpose: Health managers are responsible for planning and controlling health facilities due to the development, incorporation, and use of technologies in health systems, as well as their sustainability deriving from continuous production of goods and services. ANVISA (National Agency of Health Surveillance) introduced the Board Collegiate Resolution (RDC) No. 2 of January 25, 2010, that regulates the management of health technologies as well as the guidelines for the management of the technological park in health facilities. The purpose of this study was to develop a Health Technology Management Plan in ophthalmology according to the guidelines recommended by ANVISA. Methods: The study was based on the equipment and processes of the Secondary Reference Center for Ophthalmology (CERESO) of the Department of Ophthalmology and Visual Sciences, Federal University of São Paulo / EPM, Brazil, in 2014 and was divided into three stages. Step1: Identification and understanding of the Federal Regulation regarding the use of health technologies and their management in clinics and hospitals; Step 2: Identification of ophthalmic equipment and other technologies used at the CERESO in the Department of Ophthalmology and Visual Sciences; Step 3: Development of the Health Technology Management Plan in ophthalmology to meet the requirements of the Brazilian standards. The following equipments were identified in CERESO: optotype projector, slit lamp, Goldmann tonometer, auto-refractor, retinoscope, direct and indirect ophthalmoscopes, lensometer, electric lift chair and refractor. Results: The Health Technology Management Plan for CERESO included: a) the definitions and standardized criteria for each stage for the health technologies management process; b) detailed description of all the technical procedures involved with the technologies in use; c) appointment of a health professional responsible for implementing and monitoring the Management Plan; d) description of the roles and responsibilities of professionals involved in the processes; e) organization of a continuing education program for professionals involved in management activities. Conclusions: The Health Technology Management Plan was successfully developed for the Secondary Reference Center (CERESO) in the Department of Ophthalmology and Visual Sciences. It is a useful management tool and, respecting the characteristics of each service, can be used as a model to meet the Brazilian regulations recommended by ANVISA for public and private services.